Global, regional, and national burden of falls from 1990 to 2021: a comprehensive analysis with a focus on falls attributable to reduced bone mass and projections to 2045 - Liu, Yi; Qiu, Junjie; Huang, Renlin; Zhou, Yong; Huang, Ziqiang (Frontiers in Public Health, 2025)
BackgroundThis study aims to analyze the global epidemiological trends of falls from 1990 to 2021, providing an in-depth understanding of their evolving patterns. It explores the changing trends of falls caused by reduced bone mass in middle-aged and older adults, offering valuable insights to healthcare policymakers for more effective resource allocation.MethodsData from the Global Burden of Disease Study 2021 (GBD 2021) were used to comprehensively assess the global incidence, prevalence, mortality, and disability-adjusted life years (DALYs) associated with falls. Regions were categorized using the Socio-demographic Index (SDI), and the correlation between the fall burden and economic level was evaluated. Additionally, long-term trends were estimated using Joinpoint regression analysis, and the norpred prediction model was employed to assess future disease burden trends.ResultsFrom 1990 to 2021, the age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), age-standardized death rate (ASDR), and DALYs related to falls showed a global downward trend, although the relative number of cases continued to rise. In 1990, the ASIR was lowest in low SDI regions, while the ASDR was at an intermediate level. By 2021, the ASIR remained the lowest in low SDI regions, but the ASDR reached its highest point. From a national and regional perspective, the number of fall-related cases in 2021 almost doubled compared to 2019. The global burden of falls increased with population aging, and the disease burden is projected to continue growing over the next few decades. Analysis of falls attributable to reduced bone mass found that women's DALYs were higher than men's after the age of 50, and there was a general decreasing trend in DALYs for the 40–59 age group, followed by an increase after 2019. Decomposition analysis indicated that population growth and aging were the main factors driving the increase in incidence and mortality.ConclusionAlthough the ASIR of falls has decreased annually, the global burden continues to rise due to population growth and aging. Lack of physical activity is also a contributing factor to falls associated with reduced bone mass. Tailored prevention and treatment strategies for middle-aged and older adults are essential to reduce this burden and improve patient outcomes.